Supplementing in vitro embryo production media by NPPC and sildenafil affect the cytoplasmic lipid content and gene expression of bovine cumulus-oocyte complexes and embryos - Botigelli, Ramon Cesar [UNESP]; Razza, Eduardo Montanari [UNESP]; Pioltine, Elisa Mariano [UNESP]; Fontes, Patricia Kubo [UNESP]; Schwarz, Kátia Regina Lancellotti; Leal, Cláudia Lima Verde; Nogueira, Marcelo Fábio Gouveia [UNESP] (Elsevier, 2018)
In our study, we added natriuretic peptide type C (NPPC) and/or sildenafil during in vitro maturation (IVM) of bovine cumulus-oocyte complexes (COCs) followed by in vitro culture (IVC) of embryos with or without sildenafil. We evaluated the effects on the lipid content (LC) of oocytes and embryos and also verified the expression of 96 transcripts related to competence in matured COCs and 96 transcripts related to embryo quality in blastocysts. After IVM, LC was decreased in oocytes by NPPC while sildenafil did not affect LC in oocytes. The genes involved in lipid metabolism and lipid accumulation (DGAT1, PLIN2and PLIN3) were not affected in COCs after treatment during IVM, although the expression of PTX3 (a cumulus cells expansion biomarker) was increased and the hatched blastocyst rate was increased by NPPC during IVM. During IVM, sildenafil increased the mRNA relative abundance of HSF1 and PAF1 and decreased REST in blastocysts. The use of sildenafil in IVC increased the LC of blastocysts. The mRNA abundance in blastocysts produced during IVC with sildenafil was changed for ATF4, XBP1, DNMT3A, DNMT3B, COX2, and SOX2. Although NPPC reduced the LC of oocytes after IVM and upregulated markers for cumulus expansion, embryo production was not affected and the produced blastocysts were able to regain their LC after IVC. Finally, the use of sildenafil during IVC increased the cytoplasmic LC of embryos but did not affect embryo quality, as measured by analysis of 96 transcripts related to embryo quality.
Keywords: Cumulus-oocyte complexes; Embryos; Gene expression; Lipid content